Glial-Mediated Inflammation Underlying Parkinsonism - Carlos Barcia (Scientifica)
The interest in studying neuroimmune interactions is increasing in the scientific community, and for many researchers, immunity is becoming a crucial factor in the understanding of the physiology of the normal brain as well as the biology underlying neurodegenerative diseases. Mounting data over the last two decades point toward immune and inflammatory alterations as important mediators of the progressive dopaminergic degeneration in Parkinson’s disease. The purpose of this review is to address, under a historical perspective, as well as in the light of recent reports, the glial-mediated inflammatory and immune responses that occur in Parkinsonism. In line with this, this review also evaluates and highlights available anti-inflammatory drugs and putative targets for Parkinson’s disease therapy for the near future.